A Narrative Study of In-service EAP Teachers’ Cognition on Language Teacher Role Identities - Mahmood Reza Atai; Esmat Babaii; Behruz Lotfi Gaskaree (Iranian Journal of Language Teaching Research, 2018)
The present exploratory study probed Iranian in-service EAP teachers’ cognitions on language teacher role identities. Life history narratives and teaching philosophy statements were employed to collect qualitative data from nine Iranian in-service EAP teachers at one of the state universities in Iran. The data included the teachers’ descriptions of their teaching philosophies as well as their evaluations and interpretations of their prior teachers’ ways of being language teachers. Inductive analysis of the data allowed the researchers to identify Eight role identities including ‘teachers as creators and users of learning opportunities’; ‘teachers as selectors and users of teaching/learning materials’; ‘teachers as assessors and evaluators’; ‘teachers as researchers’; ‘teachers as realizers and facilitators of the development of learners' (full) potentials’; ‘teachers as observers of ethicality’; ‘teachers as learners’; and, ‘teachers as teacher educators’. In addition to providing a typology of teacher role identities that Iranian language teachers identify with, the study might promise some implications for language teacher education and teacher education research.